Komitmen Kerja Karyawan PT. Glico Manufacturing Indonesia - Camelia Yuliana Sitorus; Uus Md Fadli (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This article discusses the analysis of employee commitment at PT Glico Manufacturing Indonesia, a snack food company. Employee commitment is an important factor in the company's success. The purpose of conducting this research was to determine the effect of organizational commitment on the work performance of employees at PT. Glico Manifacturing Indonesia. The research method used is descriptive method, which is a problem solving procedure that is investigated by describing or describing the current situation or object of research based on visible facts or as they are. Data collection techniques are interviews and literature study. The data analysis technique is by testing the hypothesis. The results show that organizational commitment has a significant influence on the work performance of employees at PT. Glico Manufacturing Indonesia.